Pengaruh Budaya Organisasi Terhadap Inovasi dan Produktivitas - Chanzul Rijadi; Sunarto Sunarto; Jaya Mualimin (Green Publisher Indonesia, 2026)
In the midst of increasingly dynamic organizational competition, organizational culture is an important factor that can affect an organization's ability to create innovation and increase work productivity. A strong, adaptive, and creative organizational culture is believed to be able to shape more effective work behaviors and encourage the achievement of organizational goals in a sustainable manner. This research aims to analyze the influence of organizational culture on innovation and productivity within an organization. Organizational culture refers to a set of values, norms, and beliefs that guide members in performing their activities. In an increasingly competitive environment, organizations are required to foster innovation and improve productivity to maintain sustainability and competitiveness. This research employs a quantitative approach with data collected through questionnaires. The data were analyzed using statistical techniques to determine the relationship and influence between organizational culture, innovation, and productivity variables. The results indicate that organizational culture has a positive and significant effect on both innovation and work productivity. A culture that promotes openness, collaboration, and creativity is proven to enhance both individual and organizational performance. In conclusion, strengthening an adaptive and innovative organizational culture is a key factor in improving productivity and achieving sustainable organizational success